Regenerative farming and sustainable diets : human, animal and planetary health - D'Silva, Joyce; McKenna, Carol (Earthscan food and agriculture., 2024)
"This book makes the case for an urgent move away from industrial agriculture towards regenerative farming and the promotion of plant-based diets. How we produce, distribute and consume food are critical issues for the health and well-being of humans, animals and the environment. In order to develop a sustainable food system, this book argues for a radical change in farming and food consumption. Containing contributions from world renowned experts, the book promotes regenerative farming as the means to preserve planetary health, establish sustainable, healthy and secure diets and safeguard the welfare of animals. Chapters discuss broad ranging issues from climate change and biodiversity conservation to animal sentience and intensive farming, and the role of financial markets and food businesses. The book concludes with chapters discussing the routes in policy and practice to transforming the food system and achieving real-world change. This book is a must read for students, scholars and policymakers interested in establishing sustainable farming and food systems, for human health, animal welfare and environmental protection"--